Análise das dimens\~oes socioestruturais dos empreendimentos de economia solidária no Brasil - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This paper assumes that the recognition of the diversity of popular strategies for the collective generation of jobs and income is a key step in the creation of mechanisms to the promotion of their productive potential. The aim was to analyze the main information provided by the System database Solidarity Economy Information (Sies) to draw an overview of the operational structure of the social economy enterprises in Brazil. In this sense, the work focused more directly on information to provide a more comprehensive characterization of their organizational, economic and political dimensions, also trying to capture the structural differentiation factors among solidarity economy enterprises in the country. The data discussed reaffirm the hypothesis of structural heterogeneity that characterizes these enterprises.
Keywords: J54; Z13; 330; solidarity economy; collective enterprises; socio-structural dimensions; income generation; public policy